2006
DOI: 10.1177/1052562905277305
|View full text |Cite
|
Sign up to set email alerts
|

Are Heterogeneous or Homogeneous Groups More Beneficial to Students?

Abstract: This study investigated the relative benefits to the student of working in homogeneous versus heterogeneous classroom groups. Correlation analysis of 18 desirable outcomes versus 8 personality-based heterogeneity variables reveals that heterogeneity associates with advantages as well as disadvantages. Ways in which group composition might be customized to benefit students with particular needs or to emphasize particular goals are described, along with their potential downsides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 6 publications
0
26
1
Order By: Relevance
“…Why non-diverse groups may fail to establish a positive small group climate in a learning activity, while their diverse counterparts are able to, remains open for future research. These results contradict previous findings that homogeneous groups tend to be happier, experience less conflict (Ledwith et al, 1998;Schullery & Schullery, 2006) and report higher levels of motivation and success (Robbins & Fredendall, 2001), but they are consistent with other research highlighting the benefits of diverse learning groups (Schullery & Schullery, 2006;Watson et al, 1998).…”
Section: Diverse and Non-diverse Groups As Embedded Context Within Classcontrasting
confidence: 80%
See 2 more Smart Citations
“…Why non-diverse groups may fail to establish a positive small group climate in a learning activity, while their diverse counterparts are able to, remains open for future research. These results contradict previous findings that homogeneous groups tend to be happier, experience less conflict (Ledwith et al, 1998;Schullery & Schullery, 2006) and report higher levels of motivation and success (Robbins & Fredendall, 2001), but they are consistent with other research highlighting the benefits of diverse learning groups (Schullery & Schullery, 2006;Watson et al, 1998).…”
Section: Diverse and Non-diverse Groups As Embedded Context Within Classcontrasting
confidence: 80%
“…In contrast, it was expected that when the overall instructional environment consisted of less enabling collaborative contextual conditions, diverse groups composed of students coming from diverse backgrounds may experience the group assignment as more challenging and demanding than the groups composed of students from similar cultural backgrounds (Hypothesis 3). Support for Hypotheses 2 and 3 could only be tentative, since prior research on culturally diverse and non-diverse small groups has provided conflicting evidence in terms of its beneficial or detrimental implications (Ledwith et al, 1998;Robbins & Fredendall, 2001;Schullery & Schullery, 2006). Furthermore, Sweeney, Weaven, and Herington (2008) as well as Li and Campbell (2008) found that interdependent task features as well as availability of adequate teacher support are critical factors for positive multicultural group work experiences, which lends support to our expectations regarding small groups in the context of a class with a less enabling instructional environment.…”
Section: Hypothesesmentioning
confidence: 91%
See 1 more Smart Citation
“…According to a meta-analysis by Richter (2011), teamwork turns out to be an effective means for improving productivity in organizations. Parallel with the increased popularity of teams in organizations, student team projects are now common in the educational curriculum (Amato & Amato, 2005;Schullery & Schullery, 2006). Learning in groups, or collaborative learning, has been linked to improved learning, higher order thinking skills, higher grades and better preparation for the workplace (Horsburgh, Lamdin, & Williamson, 2001;Shimazoe & Aldrich, 2010).…”
Section: Theoretical Frameworkmentioning
confidence: 98%
“…These millennials are said to be the most diverse generation ever (DeBard, 2004) and they have been influenced in their way of processing information and interacting with peers due to their exposure to technology (Prensky, 2001). With the entry of this cohort in higher education, combined with the increased prevalence of teamwork in the modern educational and organizational environment (Bar, Niessen, & Ruenzi, 2008;Schullery & Schullery, 2006), it is vital that we understand these diverse ways of thinking and the influence they have on interactions.…”
Section: Introductionmentioning
confidence: 99%